EVALUATION OF FERTILITY PERFORMANCE IN IRAQI MARES - R. Abdul-Aziz, F.; Y.A. Al-Rahman, L.; M. Hasson , T. (The Iraqi Journal of Veterinary Medicine, 1992)
Between August, 1989, to July, 1990, 874 Iraqi mares aged between (3-25) years were examined by rectal palpation to diagnose pregnancy in order to evaluate their reproductive efficiency. These mares were grouped according to their reproductive status into Lactating, Maiden and Barren. The mean overall pregnancy rate was 33.75% and the monthly rate ranged between 14%-55.5%. Pregnancy rates were 45%, 33.8% and 25.4% respectively. We conclude that pregnancy rate could be used to evaluate reproductive efficiency of Iraqi mares. Higher pregnancy rate can be obtained when mares serviced during Spring and Autumn months